การวิเคราะห์หาสีของเสื้อผ้าที่เหมาะสมกับสีผิว - ณัฐพัชร์ ศิริภาธนพัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This study investigated personal colour for clothes, in which personal colour for each subject was evaluated using four groups of colour clothes adhering to four seasons: spring, summer, winter and autumn. There were 35 subjects in total. The skin tone of each subject was matched with Pantone Skin Tone Chart and was measured with a spectrophotometer. The pictures of each subject with either one of the four season clothes colours in turn were taken and presented to observers online for evaluation. The results showed that the agreement between the evaluations by observers and by the experimenters was 40%. The matching Pantone Skin Tone samples with the subjects’ skin colours could not be used to group the skin tone. Analyses of skin colour values showed that subjects with personal colour of Winter had reddish skin with high chroma and lightness from low to high; Summer – yellowish skin with low chroma and lightness from low to high; Spring – neutral skin with chroma from low to high; and Autumn – skin colour from reddish to yellowish with high chroma.